Comparação de latência e duração do bloqueio do nervo alveolar inferior aplicado pela seringa carpule ou pelo dispositivo Morpheus® - Silveira, Maria Paula Mendonça (2019)
Introduction: Due to the administration of local anesthetics, pain is the main reason why patients avoid dental procedures. To minimize these effects, the systems of electronically controlled anesthetic injection appeared. The present study aimed to compare latency and duration of inferior alveolar nerve block delivered by the carpule syringe or the Morpheus® computerized system. Materials and Methods: This study was a split- mouth, double-blind, randomized clinical trial with 31 volunteers who required restorative treatment in dental units 37 and 47. The inferior alveolar nerve block was performed with carpule syringe and Morpheus® device. Then, the teeth had latency times and duration of anesthesia measured using the pulp electric tester. The Visual Analogue Scale (VAS) questionnaire assessed the degree of pain experienced during the two anesthetic methods and the preference of the volunteers for the injection device. All data were tabulated and sent for statistical analysis with a level of significance set at 5%. Results: The latency time were the same for most cases (2 minutes). The duration of the anesthetic effect was higher for the carpule technique, but with no statistically significant difference between the groups. The success rate for the carpule technique was 80.65% and failure rate was 19.35%. For the technique with Morpheus®, the percentage of success was 83.87% and of failure of 16.13%. There were no significant differences in pain after injection. Most of the volunteers preferred the anesthetic technique with Morpheus® (64.52%), while 35.48% preferred the carpule syringe. Conclusion: The techniques with carpule and Morpheus® presented same time of latency and anesthetic duration, as well as similar success rate. In addition, the pain experienced during the execution of the two techniques was the same. As for the preference for the injection devices, the majority opted for Morpheus® system.